PENYALAHGUNAAN WEWENANG PENERIMA KUASA DALAM PERJANJIAN PERIKATAN JUAL BELI TANAH DAN KUASA MENJUAL (Putusan Nomor : 173/K/Pdt/2012) - Mita Ardianti; I Gusti Ayu Ketut Rachmi Handayani (Jurnal Repertorium, 2018)
AbstractThe objective of this article are to investigate based of the judge's consideration in deciding the case of abuse of authority of the power of attorney in the agreement of sale and purchase of land and the power of selling (verdict number: 173/K/Pdt/2012). This article is a normative juridical article, which is in the form of diagnostic and perspective that is to examine the principles of law, and legal systematics. Based on the result of the article and discussion it can be concluded that the abuse of authority done by the authorized party in the agreement of sale and purchase of land and the power of sale is not disputed by the judge and keeps running as it should. The heirs of the power of attorney in this matter shall not enjoy legal protection from the decision of the Supreme Court and shall not be compensated for any damages resulting from the abuse of power they have undergone. Based on the decision of the Supreme Court it is expected that the judge in deciding cases using applicable laws and regulations must follow and understand the values of law and sense of justice that lives in the community.Keywords: Power of Sale, Sale and Purchase Agreement, Misuse of Authority.AbstrakTujuan penulisan artikel ini adalah untuk mengetahui latar belakang pertimbangan hakim dalam memutus perkara penyalahgunaan wewenang penerima kuasa dalam perjanjian perikatan jual beli tanah dan kuasa menjual (putusan nomor : 173/K/Pdt/2012). Penelitian ini bersifat yuridis normatif, yang berbentuk diagnostik dan perspektif yaitu meneliti asas-asas hukum, dan sistematika hukum. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa penyalahgunaan wewenang yang dilakukan oleh penerima kuasa dalam perjanjian perikatan jual beli tanah dan kuasa menjual tidak dipermasalahkan oleh hakim dan tetap berjalan sebagaimana mestinya. Ahli waris pemberi kuasa dalam hal ini tidak mendapatkan perlindungan hukum dari putusan Mahkamah Agung tersebut dan tidak mendapatkan ganti rugi atas kerugian akibat penyalahgunaan pemberian kuasa. Berdasarkan putusan Mahkamah Agung tersebut diharapkan agar hakim dalam memutus perkara menggunakan peraturan undang-undang yang berlaku serta harus mengikuti dan memahami nilai-nilai hukum dan rasa keadilan yang hidup di masyarakat.Kata Kunci: Kuasa Menjual, Perjanjian Perikatan Jual Beli, Penyalahgunaan Wewenang.